Context and violence in individual prayers for protection - Firth, D. G. (Verbum et ecclesia, 1997)
The individual prayers for protection within the Psalter are marked by a consistency in terms of the context supposed and the nature of violence experienced by the psalmists. Consistently, these psalms also assert that the right to retributive violence against the enemies belongs to Yahweh alone. Such a consistent pattern indicates that those responsible for assembling the Book of Psalms intended to model this as the appropriate response for the faithful.